Adaptación de la Escala de Percepción Global de Estrés en universitarios de Beca 18 - Guzmán Yacaman, Jaime Enrique (2016)
The aim of this paper consisted on adapt the Global Perceived Stress Scale on a Peruvian population of college students of the program Beca 18, by the report of psychometric properties. First, the scale was reviewed by judges, secondly, a linguistic comparison was made by using the scales adapted in Chile and Mexico, and in third place a double translation with the original version, was done. A pilot test was realized and finally the scale was applied to a total of 332 college students. By a principal component analysis, two factors were found and the item 12 was taken out. The bifactorial model of the EPGE-13 was confirmed doing an CFA. Using the SPANAS, convergent and divergent validity evidences, were obtained. Likewise, the scale demonstrate adequate reliability (internal consistency, α = .79 for the factor of eustress and α =.77 for the factor of distress). Demographic results indicated that there was a major presence of perceived stress in women than in men. Nevertheless, there were not significant differences between stress and birthplace.